BUSINESS COMMUNICATION IN CORPORATE BRANDING ON SOCIAL MEDIA - Rizka Ar Rahmah; Desiana (Department of Islamic Communication and Broadcasting - Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
This qualitative study on Business Communication in Corporate Branding on Social Media explores diverse communication strategies employed by companies to build and maintain their brand identity on various social media platforms. The research, employing a purposive sampling strategy, engages professionals from diverse industries through in-depth semi-structured interviews and content analysis of corporate social media posts. The findings indicate a dynamic spectrum of communication approaches, including promotional content, interactive campaigns, and informative posts. Challenges in maintaining consistency across platforms emerge, emphasizing the need for adaptable strategies. Visual elements play a significant role, with images and videos serving as powerful tools for conveying brand messages. Crisis management on social media is identified as a crucial aspect, prompting the need for proactive strategies during crises. Employee advocacy programs prove instrumental in amplifying brand messages, contributing to a more authentic brand image. Positive consumer perceptions and loyalty are linked to engaging content and transparent communication. Cultural nuances in communication strategies and the identification of long-term trends and shifts underscore the importance of adaptive and culturally sensitive approaches. These findings provide valuable insights for businesses navigating the dynamic landscape of social media branding, offering practical implications for optimizing communication strategies and fostering positive corporate brand images.